Microsurgical techniques in temporal lobe epilepsy. (April 2017) - Alonso Vanegas, Mario A.; Lew, Sean M.; Morino, Michiharu; Sarmento, Stenio A.
Summary: Temporal lobe resection is the most prevalent epilepsy surgery procedure. However, there is no consensus on the best surgical approach to treat temporal lobe epilepsy. Complication rates are low and efficacy is very high regarding seizures after such procedures. However, there is still ample controversy regarding the best surgical approach to warrant maximum seizure control with minimal functional deficits. We describe the most frequently used microsurgical techniques for removal of both the lateral and mesial temporal lobe structures in the treatment of medically intractable temporal lobe epilepsy (TLE) due to mesial temporal sclerosis (corticoamygdalohippocampectomy and selective amygdalohippocampectomy). The choice of surgical technique appears to remain a surgeon's preference for the near future. Meticulous surgical technique and thorough three‐dimensional microsurgical knowledge are essentials for obtaining the best results.